Editorial: Leveraging gender, youth and social networks for inclusive and transformative livestock production in the tropics and subtropics - Triana Ángel, Natalia; Burkart, Stefan (Frontiers Media, 2024)
The Research Topic titled “Leveraging Gender, Youth, and Social Networks for Inclusive and Transformative Livestock Production in the Tropics and Subtropics” is an exploration of the interconnected social dynamics that shape livestock systems in these regions. The articles within this Research Topic underscore the necessity of integrating social factors such as gender roles, youth engagement, and community networks into the broader agenda of sustainable livestock production.